2003
DOI: 10.1136/heart.89.10.1179
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the   myosin heavy chain gene in hypertrophic cardiomyopathy: critical functional sites determine prognosis

Abstract: Objectives: To assess patients with different types of mutations of the β myosin heavy chain (β MHC) gene causing hypertrophic cardiomyopathy (HCM) and to determine the prognosis of patients according to the affected functional domain of β MHC. Design and setting: Cohort study of subjects referred to an HCM clinic at an academic hospital. Patients: 70 probands from the HCM clinic were screened for mutations of the β MHC gene and 148 family members of the genotype positive probands were further assessed. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 42 publications
1
36
0
4
Order By: Relevance
“…It has been suggested that mutations in the head or neck regions are more likely to cause a severe outcome, but these conclusions were drawn from relatively small cohorts [40,42]. It is apparent from the data presented in figure 2 that a notably larger proportion of malignant phenotypes arise as a result of mutations in the head region (49%) compared to the tail (20%).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…It has been suggested that mutations in the head or neck regions are more likely to cause a severe outcome, but these conclusions were drawn from relatively small cohorts [40,42]. It is apparent from the data presented in figure 2 that a notably larger proportion of malignant phenotypes arise as a result of mutations in the head region (49%) compared to the tail (20%).…”
Section: Discussionmentioning
confidence: 75%
“…Some studies support this hypothesis [2,40,42], while others do not find a correlation [50,81]; however, these studies were performed in relatively small cohorts. The data described in the present analysis of 70 missense mutations does, to a certain degree, support this correlation.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Interaction of this segment of intact myosin with F-actin appears to be nucleotide-dependent and a critical contribution to the strong binding of myosin to actin (3,4,(7)(8)(9). This region of myosin further contains sites of mutation (residues 403, 404, and 411) that are associated with hypertrophic cardiomyopathy (18,32). However, care should be exercised in extrapolating the results obtained with isolated fragments to properties associated with the intact myosin head.…”
Section: Discussionmentioning
confidence: 99%